A turn-on fluorescence aptasensor based on carbon dots for sensitive detection of adenosine. (31st July 2017) - Shen, Xin; Xu, Lei; Zhu, Wanying; Li, Bingzhi; Hong, Junli; Zhou, Xuemin
Abstract : A novel turn-on fluorescence aptasensor was designed for adenosine detection based on FRET from ssDNA-CDs to aptamer-AuNPs. Abstract : In this paper, a novel turn-on fluorescence aptasensor has been designed for adenosine detection based on fluorescence resonance energy transfer (FRET) from single-stranded DNA labeled carbon dots (ssDNA-CDs) to aptamer modified gold nanoparticles (aptamer-AuNPs). In the absence of adenosine, the fluorescence of ssDNA-CDs was quenched by aptamer-AuNPs via the formation of an aptamer–ssDNA duplex. The introduced adenosine competed to displace ssDNA-CDs by specifically binding to the aptamer, resulting in the recovery of the quenched fluorescence of ssDNA-CDs. Under optimized conditions, the increase in fluorescence intensity was proportional to the concentration of adenosine with a linear range of 10–500 nM and allowed a limit of detection as low as 4.2 nM. In addition, this method was successfully applied to adenosine determination in human serum samples with satisfactory results.